The complete mitochondrial genome of the pirarucu (Arapaima gigas, Arapaimidae, Osteoglossiformes) - Hrbek,Tomas (2008)
We sequenced the complete mitochondrial genome of the pirarucu, Arapaima gigas, the largest fish of the Amazon basin, and economically one of the most important species of the region. The total length of the Arapaima gigas mitochondrial genome is 16,433 bp. The mitochondrial genome contains 13 protein-coding genes, two rRNA genes and 22 tRNA genes. Twelve of the thirteen protein-coding genes are coded on the heavy strand, while nad6 is coded on the light strand. The Arapaima gene order and content is identical to the common vertebrate form, as is codon usage and base composition. Its control region is atypical in being short at 767 bp. The control region also contains a conserved ATGTA motif recently identified in the Asian arowana, three conserved sequence blocks (CSB-1, CBS-2 and CBS-3) and its 3' end contains long series of di- and mono-nucleotide microsatellite repeats. Other osteoglossiform species for which control region sequences have been published show similar control region characteristics.